2020
DOI: 10.1111/jfpp.14820
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mannanase activity on viscosity in different gums

Abstract: Cellulose, hemicellulose, and lignin are basic components of the plant cell wall. Hemicelluloses, which includes xyloglucans, xylans, mannans, glucomannans, β-1,3, and β-1,4-glucans, are polysaccharides linking cellulose and lignin in the plant cell wall (Scheller & Ulvskov, 2010). Mannan is one of the major hemicellulose component softwood and bean seed includes mannans as glucomannan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Erkan et al. (2020) reported a significant decrease in viscosity on Locust bean gum and guar gum with the use of β‐mannanase. This results showed that the cellulase enzyme can be used for gum modification and confirmed the structural changes occurring during hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Erkan et al. (2020) reported a significant decrease in viscosity on Locust bean gum and guar gum with the use of β‐mannanase. This results showed that the cellulase enzyme can be used for gum modification and confirmed the structural changes occurring during hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported that enzymatic treatment leads to a reduction on chain length and molar mass of galactomannans (Buriti et al, 2014;Jian et al, 2013;Mudgil et al, 2012aMudgil et al, , 2014, and this also explained the reduction in viscosity. Erkan et al (2020) reported a significant decrease in viscosity on…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…is in the status of Generally Recognized as Safe, its products are also widely used in the food, cosmetics, pharmaceutical, medical, and biofuel industries. [4][5][6] Many researchers have used it in their studies to produce enzymes such as inulinases, [4][5][6][7][8][9][10][11][12] βmannanases and mannooligosaccharides, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] protease, 28 lipase, 29 polygalacturonase, 30 amylase, 31 cellulase, 32 and xylanase. 33 Regarding mathematical modeling, the estimation of the observed values of the fermentations regarding inulinase production has been made.…”
Section: Introductionmentioning
confidence: 99%
“…is in the status of Generally Recognized as Safe, its products are also widely used in the food, cosmetics, pharmaceutical, medical, and biofuel industries 4–6 . Many researchers have used it in their studies to produce enzymes such as inulinases, 4–12 β‐mannanases and mannooligosaccharides, 13–27 protease, 28 lipase, 29 polygalacturonase, 30 amylase, 31 cellulase, 32 and xylanase 33 …”
Section: Introductionmentioning
confidence: 99%